Innovative use of squid (Loligo spp.) ink powder as a potent immunostimulant for vannamei shrimp (Litopenaeus vannamei) in the treatment of infectious myonecrosis - Mohamad Fadjar; Hartmut Kühn; Ayu Winna Ramadhani; Diana Aisyah; Cucun Herlina; Rangga Idris Affandi; Jefri Anjaini (Veterinary World)
Background and Aim: Infectious myonecrosis virus (IMNV) is a significant pathogen affecting Litopenaeus vannamei, causing high mortality and substantial economic losses in shrimp aquaculture. Conventional chemotherapeutics have limited efficacy and raise environmental concerns. This study explores the immunostimulatory potential of squid (Loligo spp.) ink powder as a natural dietary supplement to enhance the nonspecific immune responses in L. vannamei and mitigate IMNV-associated pathology.